Mengetahui Adanya Pengaruh Pemanfaatan Teknologi Ponsel Dan Smart Phone Terhadap Peningkatan Produktifitas Industri Rumahan Di Lombok - Muhammad Munawir Gazali; Heroe Santoso; Raisul Azhar (Universitas Bumigora, 2019)
The implementation of Productivity Enhancement activities for Home Industry players (HI) through Information Communication of Technology (ICT) or Utilization of Information and Communication Technology (ICT) is a program of the Ministry of Women's Empowerment and Child Protection (KPPPA) in collaboration with the Association of Higher Education Informatics and Computers ( APTIKOM). This program was carried out in order to improve the economy of women, so that home industry players in Indonesia, especially in West Nusa Tenggara (NTB) in order to develop better and more able to increase productivity and computer science. With ICT training, it will certainly be able to improve its quality especially in utilizing technology or the digital era in an effort to market products by no longer using manual systems. With the digital era, IRs can market their products with On Line systems. Especially in the face of the era of globalization, they will be able to take advantage of existing sites, how to find products, how to determine the price of how to create e-mails and how to use social media or to develop creative businesses.